A real communication based on art: the recovery of beauty and symbol, According to Marko Ivan Rupnik’s Conception - Ruiz de Loizaga Martín, María (Pensamiento. Revista de Investigación e Información Filosófica, 2021)
According to Marko Ivan Rupnik, art should reveal the beauty in truth and good. The interrelationships among these concepts have a variety of implications, such as beauty coinciding with the state of fullness of the being. Furthermore, beauty and communication cannot be separated from each other. To the extent communication —and beauty— represents an outward projection towards others, it unveils an undercurrent essence of restoration of symbolism. Rupnik firmly believes that the real work of art must present a symbolic conception. Form is joined to content, thus only if we contemplate the work, can we arrive to the full extent of the knowledge contained in the work. Rupnik’s conceptions of beauty and symbol are influenced by 19th and 20th century Eastern Europe authors. Their work helps us understand comprehensively the mosaics created by Rupnik, as the director of the Centro Aletti.
Keywords: Marko Ivan Rupnik; Centro Aletti; beauty; symbol; art